Predicting molecular properties of α‐synuclein using force fields for intrinsically disordered proteins. Issue 1 (19th August 2022) - Pedersen, Kasper B.; Flores‐Canales, Jose C.; Schiøtt, Birgit
Abstract: Independent force field validation is an essential practice to keep track of developments and for performing meaningful Molecular Dynamics simulations. In this work, atomistic force fields for intrinsically disordered proteins (IDP) are tested by simulating the archetypical IDP α‐synuclein in solution for 2.5 μs. Four combinations of protein and water force fields were tested: ff19SB/OPC, ff19SB/TIP4P‐D, ff03CMAP/TIP4P‐D, and a99SB‐disp/TIP4P‐disp, with four independent repeat simulations for each combination. We compare our simulations to the results of a 73 μs simulation using the a99SB‐disp/TIP4P‐disp combination, provided by D. E. Shaw Research. From the trajectories, we predict a range of experimental observations of α‐synuclein and compare them to literature data. This includes protein radius of gyration and hydration, intramolecular distances, NMR chemical shifts, and 3 J‐couplings. Both ff19SB/TIP4P‐D and a99SB‐disp/TIP4P‐disp produce extended conformational ensembles of α‐synuclein that agree well with experimental radius of gyration and intramolecular distances while a99SB‐disp/TIP4P‐disp reproduces a balanced α‐synuclein secondary structure content. It was found that ff19SB/OPC and ff03CMAP/TIP4P‐D produce overly compact conformational ensembles and show discrepancies in the secondary structure content compared to the experimental data.